2014
DOI: 10.1073/pnas.1414659111
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to elevated CO 2 enhances plant community stability by suppressing dominant plant species in a mixed-grass prairie

Abstract: Climate controls vegetation distribution across the globe, and some vegetation types are more vulnerable to climate change, whereas others are more resistant. Because resistance and resilience can influence ecosystem stability and determine how communities and ecosystems respond to climate change, we need to evaluate the potential for resistance as we predict future ecosystem function. In a mixed-grass prairie in the northern Great Plains, we used a large field experiment to test the effects of elevated CO 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 66 publications
4
85
0
Order By: Relevance
“…; Zelikova et al . ), changes in allocation patterns from shoots to roots (Suter et al . ) and nitrogen limitation, can all suppress the stimulatory effects of elevated CO 2 (Luo et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Zelikova et al . ), changes in allocation patterns from shoots to roots (Suter et al . ) and nitrogen limitation, can all suppress the stimulatory effects of elevated CO 2 (Luo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Grassland primary production has increased with warming in cold regions, but has decreased in hot regions4141516. In general, grassland primary production is extremely sensitive to precipitation and temperature changes, and to non-climate factors including grazing, fires, nitrogen deposition, and rising CO 2 levels417. Uncertainty in the response of grassland primary production to climate change and other perturbations remains a major impediment to assessing causal relationships, and to determining the levels of permissible climate change4.…”
mentioning
confidence: 99%
“…Emer and collaborators (2013) showed that changes in the structure of interacting plant and animal communities are important for interaction network structure. Meanwhile, climate variation has been highlighted as an important factor shaping plant and animal communities across spatial and temporal scales (Zelicova et al 2014, Diamond et al 2016. Meanwhile, climate variation has been highlighted as an important factor shaping plant and animal communities across spatial and temporal scales (Zelicova et al 2014, Diamond et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, climate variation has been highlighted as an important factor shaping plant and animal communities across spatial and temporal scales (Zelicova et al 2014, Diamond et al 2016. However, recent studies have proposed that plant and ant communities appear to be stable temporally even under climate change scenarios (Zelicova et al 2014, Donoso 2017. However, recent studies have proposed that plant and ant communities appear to be stable temporally even under climate change scenarios (Zelicova et al 2014, Donoso 2017.…”
Section: Discussionmentioning
confidence: 99%